An Internet-based survey of the dance fitness program OULA. (20th July 2018) - Hellem, Tracy; Ferguson, Hayden
Background: OULA is a high-energy dance workout to top 40 hits that is inspired by yoga and non-impact aerobics. Created in Missoula, Montana, the program has been gaining national and international popularity. To understand the demographic composition, reasons for attending OULA, and experiences with depression/anxiety, we conducted an Internet-based survey. Methods: A pilot descriptive cross-sectional Internet-based survey was created in Qualtrics and distributed through social media and flyers. Results: The 38-item survey received responses from 302 participants. Current OULA participants chose "exercise" as the primary reason for attending (40.2%, 95% confidence interval: 33.3–48.2), followed by "stress relief/improve mood" (28.8%, 95% confidence interval: 23.0–35.6). Participants listed "stress relief/improve mood" as the most common secondary (35.6%, 95% confidence interval: 29.0–43.2) and tertiary (38.6%, 95% confidence interval: 31.7–46.7) reason for attending OULA. A majority of the participants said that OULA makes them feel like part of a community (93.2%, 95% confidence interval: 82.5–105.1) and increases their energy outside of class (80.1%, 95% confidence interval: 70.2–91.1). In our sample, 12.5% (95% confidence interval: 8.8–17.1) and 9.0% (95% confidence interval: 5.9–12.9) were currently taking antidepressants and anxiolytics, respectively. Conclusion: These results suggest that current OULA participants are already using the program to relieve stress or improve mood. Further research should be conducted to understand the relationship between OULA and depression/anxiety.